The Effect of The Teachers’ Inspirational Behavior on The Students’ Self-Directed Learning - Prianto, Agus; Hamidah, Riful; Soedarto, Achmad; Hartati, Retno Sri; Nisak, Dian Khoirun (FKIP Universitas Lampung, 2021)
The Effect of The Teachers’ Inspirational Behavior on The Students’ Self-Directed Learning. Objectives: This study intends to examine the effect of the teachers’ inspirational behavior on the students’ self-directed learning. Methods: The data analysis use a descriptive approach to describe the teacher’s inspirational behavior and the level of student’s self-directed learning. This study used analysis of variance and regression techniques to examine the relationship between inspirational behavior and self-directed learning. Findings: Several indicators of inspirational behavior that have a dominant influence in forming students’ self-directed learning, namely: the ability of teachers to stimulate students, to create an exciting learning atmosphere, to motivate students, to deliver up to date material, and to carry out learning innovatively and creatively. Conclusion: This study concludes that the teachers’ inspirational behavior has a positive effect on the students’ self-directed learning.Keywords: Inspirational behavior, ability to stimulate, motivation, self-directed learning. DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202110